The acquisition of future temporality by L2 French learners. Issue 2 (July 2014) - AYOUN, DALILA
ABSTRACT This cross-sectional study in the acquisition of future temporality by English-speaking L2 French learners presents a descriptive account of the major contrastive features of the expression in futurity in English and French before considering learnability implications. A personal narrative and a cloze task were administered to L2 French learners (n = 34) at three proficiency levels and French native speaker controls (n = 14). Analyses revealed task and proficiency effects, but all learners used a variety of morphological forms to express futurity in their personal narratives, and appear to be acquiring temporal and modal values associated with the future.